Learner Behaviour in a MOOC Practice-oriented Course: In Empirical Study Integrating TAM and TPB - Yang, Hsi-Hsun; Su, Chung-Ho (International Review of Research in Open and Distributed Learning, 2017)
Few practice-oriented courses are currently integrated into online learning platforms, such as OpenCourseWare, Khan Academy, and Massive Open Online Courses (MOOCs). It is worthwhile to explore how learners respond to information technology and new teaching methods when practice-oriented course are placed online. Therefore, this study probes learner willingness to participate in a practice-oriented course distributed through a MOOC platform, investigating relationships among perceptions, behavioural intentions, and actual behaviour. The current research framework integrates the Technology Acceptance Model and the Theory of Planned Behavior as its core theoretical basis. Empirical data were collected through a cross-section survey. All participants were students of 2D Animation Production, with a total of 272 respondents. The questionnaire data used Partial Least Squares Structural Equation Modeling (PLS-SEM) analysis. Results show: (a) attitude exerted the greatest influence on learners’ behavioural intention; (b) learners’ perceived behaviour control, subjective norm, and attitude, which directly and positively influence their behavioural intention; (c) behavioural intention exhibited dual mediation effects; (d) behavioural intention positively influenced actual behaviour in the C-TAM-TPB model, with a high level of overall model fit.